Peningkatan Kreatifitas Anak TK Dengan Pemanfaatan Sampah dan Barang Bekas Sebagai Media Pembelajaran - Kuswati, Dian Yuli Kuswati (Universitas Sarjanawiyata Tamansiswa, 2024)
The problem of the large amount of waste around Mutiara Bunda Kindergarten, especially because of its location close to the TPA (Final Disposal Site), encourages the need for solutions to manage inorganic waste such as plastic, used bottles, cans, and cardboard. This study aims to increase the utility value of waste while spurring the creativity of children at Mutiara Bunda Kindergarten Baleharjo, Wonosari, Gunungkidul. The study was conducted through location observation, collaboration with TPA managers, teachers, parents, and school committees. Activities were integrated with the curriculum, utilizing used goods to increase children's creativity in learning and playing. The steps include preparing materials and tools, implementing activities, and evaluating and following up. The results of the study showed that the utilization of used goods significantly increased the utility value of waste, reduced waste, and supported children's creativity. Learning media from used goods helped clarify the material, motivated children to be more active, and increased cooperation. With good planning, the use of used goods can support the learning process effectively, facilitate the delivery of messages, and achieve learning goals. Optimizing these benefits is highly dependent on the teacher's ability to select and use learning media according to the goals and functions of education.